Regularization by nonlocal conditions of the incorrect problems for differential‐operator equations of the first order - Yurchuk, N. I.; Mousa, Ababneh (Mathematical Modelling and Analysis, 1997)
“Regularization by nonlocal conditions of the incorrect problems for differential‐operator equations of the first order” Mathematical Modelling Analysis, 2(1), p. 160-166. First Published Online: 14 Oct 2010